Kepemimpinan dalam Evaluasi Pendidikan Islam - Reindo Febrianto; Yola Septia Utami; Retno Ambar Wati; Desy Eka Citra Dewi (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
Leadership in Islamic education evaluation plays a pivotal role in ensuring that evaluation processes are aligned with Islamic values and contribute significantly to improving the overall quality of education. This study discusses the conceptual foundations, essential functions, and strategic implementation of leadership in evaluation within Islamic education institutions. Using a qualitative descriptive approach supported by literature analysis, the research identifies key principles such as justice (al-‘adl), trust (amanah), and responsibility (mas’uliyyah) as core components of effective leadership in the evaluation process. These principles are not only theoretical but also deeply embedded in the ethos of Islamic education. The findings highlight that an Islamic-based leadership model in evaluation fosters not only intellectual excellence but also promotes spiritual, ethical, and moral development among learners. Furthermore, this study emphasizes the importance of participatory, transparent, and data-driven leadership strategies that are firmly grounded in Islamic ethical values to enhance institutional accountability, stakeholder trust, and the pursuit of continuous quality improvement. Ultimately, this research provides a framework for integrating Islamic leadership principles into evaluation practices to ensure a holistic and transformative educational experience.